Optimalisasi Penyerapan Aspirasi Masyarakat dalam pelaksanaan Musyawarah Desa di Negeri Suli - Natanel Lainsamputty; Benyamin Charel Picauly (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2021)
This paper uses a normative legal research method because the focus of the study departs from the vagueness of norms, using the approaches: statute approach, conceptual approach, and analytical approach, and the results of this paper regulate that village consultations are the authority of the Village Consultative Body, or what is called the Negeri Suli Government. namely Saniri authority. The Village Deliberation is a deliberation related to strategic matters so that it cannot be ruled out, the fact that has occurred over a period of 7 years since the Village Fund was disbursed, the Negeri Suli Government has neglected the stages of the Village Deliberation, and this has greatly impacted the sub-optimal development process. in the Suli country. Village deliberations aim to maximize the aspirations of the community which will be implemented through targeted government work programs